The Role of Supreme Court Circular Letters (SEMA) in Shaping Judges’ Ratio Decidendi on the Scope of General Attachment in Indonesian Bankruptcy Law - Ulhaq (Indonesian Journal Publisher, 2026)
Differences in the interpretation of the scope of general seizure in bankruptcy cases in Indonesia have created legal uncertainty, particularly regarding the distinction between the assets of the bankrupt debtor and those of third parties. In commercial court practice, judges rely not only on statutory regulations but also on Surat Edaran Mahkamah Agung (SEMA) as interpretive references, giving rise to debate over their position as a source of law. This study aims to analyze the influence of SEMA, particularly SEMA Number 2 of 2024, on the formation of judges' ratio decidendi in interpreting general seizure in bankruptcy. This research adopts a normative juridical method using statutory, conceptual, and case approaches, through a prescriptive-analytical examination of primary and secondary legal materials. The findings indicate that SEMA functions as an interpretive guideline that significantly influences judges' legal reasoning in limiting the scope of general seizure to the assets of the bankrupt debtor, despite lacking formal status within the hierarchy of laws and regulations. The study also reveals variations in the use of SEMA depending on judges' interpretive approaches and value orientations in adjudication, where some prioritize strict legal certainty while others emphasize substantive justice. This research contributes to a broader understanding of the dynamics of legal sources in judicial practice and underscores the role of SEMA in promoting consistency in judicial decisions, filling legal gaps, and strengthening legal certainty in complex bankruptcy cases involving third-party interests.